2010
DOI: 10.1051/0004-6361/200912227
|View full text |Cite
|
Sign up to set email alerts
|

The solar photospheric abundance of carbon

Abstract: Context. The analysis of the solar spectra using hydrodynamical simulations, with a specific selection of lines, atomic data, and method for computing deviations from local thermodynamical equilibrium, has led to a downward revision of the solar metallicity, Z. We are using the latest simulations computed with the CO5BOLD code to reassess the solar chemical composition. Our previous analyses of the key elements, oxygen and nitrogen, have not confirmed any extreme downward revision of Z, as derived in other wor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 37 publications
(70 reference statements)
9
94
3
Order By: Relevance
“…The heavy-element abundance was revised to Z/ X=0.0181 and Z=0.0134 , hereafter AGS09), Z/X=0.0191 and Z=0.0141 (Lodders et al 2009), and Z/X=0.0211 and Z=0.0154 (Caffau et al 2010). Compared to the SSMs with GS98 mixtures, solar models constructed in accordance to the AGS09 mixtures also disagree with the seismically inferred sound-speed and density profiles, CZ depth, and CZ helium abundance Guzik & Mussack 2010;Serenelli & Basu 2010;Turck-Chièze et al 2010Bi et al 2011;Serenelli et al 2011;Lopes & Turck-Chièze 2013, 2014Le Pennec et al 2015).…”
Section: The Constraints Of Helioseismologymentioning
confidence: 99%
“…The heavy-element abundance was revised to Z/ X=0.0181 and Z=0.0134 , hereafter AGS09), Z/X=0.0191 and Z=0.0141 (Lodders et al 2009), and Z/X=0.0211 and Z=0.0154 (Caffau et al 2010). Compared to the SSMs with GS98 mixtures, solar models constructed in accordance to the AGS09 mixtures also disagree with the seismically inferred sound-speed and density profiles, CZ depth, and CZ helium abundance Guzik & Mussack 2010;Serenelli & Basu 2010;Turck-Chièze et al 2010Bi et al 2011;Serenelli et al 2011;Lopes & Turck-Chièze 2013, 2014Le Pennec et al 2015).…”
Section: The Constraints Of Helioseismologymentioning
confidence: 99%
“…A description of these models can be found in . We computed 3D corrections as described in and in Caffau et al (2010).…”
Section: Model Atmospheres and Atomic Datamentioning
confidence: 99%
“…In column 9 [S/Fe] is given; both NLTE and ∆ (2) 3D corrections are applied. We adopt A(S)=7.16 for the solar sulphur abundance, as described in Caffau et al (2010). In column 10 the sulphur abundance from Caffau et al (2005) is reported, and in column 11 there is the relative NLTE correction from Takeda et al (2005).…”
Section: Analysis Of Crires Datamentioning
confidence: 99%
“…. ± = ε [5] and [8], especially given the very small errors in the determinations of ( ) C logε in Refs. 6, 5, and 8.…”
Section: Introductionmentioning
confidence: 99%